2010, Nr. 7, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Accounting theory and practice Kristina Rudžionienė, Accounting: a science or an art?, 9Jonas Mackevičius, Vilius Savickas, The issue of management accounting content, 17Accounting teaching methodologyRasa Subačienė, Daiva Raziūnienė, The analysis of process of revenue accounting in Lithuanian authors‘ textbooks, 28Kostas Valužis, Necessary usage of uniform accounting model during the teaching process, 36Vida Vitartaitė, Indrė Knyvienė, Applying the case study method in the course of accounting, 46Training of accounting specialistsValentinas Bružauskas, Danutė Zinkevičienė, Suggestions for the improvement of financial – accounting undergraduates studies, 51Ona Gudaitienė, Melanija Sinevičienė, The benefits of the final practice for the future accountants, 63Beata Harasim, Concern in studying accounting in Poland, 72Gintarė Jakštonytė, Lukas Giriūnas, Evaluation of an accountant‘s professional skills and abilities, 76Kristina Kundelienė, Lina Dagilienė, Vytautas Boguslauskas, Topicality of accounting specialists training at Kaunas university of technology, 83Deimantė Kviklienė, Fausta Smolenskienė, Analysis of accounting subjects in the context of accounting study programme in case of Šiauliai state college, 91Vaclovas Lakis, Transformation of accounting and auditing study at Vilnius university, 100Romualdas Valkauskas, Developing the abilities of accounting specialists and theory of statistical conclusions, 113Economical problemsEdvardas Makšeckas, Auksė Makšeckienė, Relevance,  need and quality assurance of training: agricultural education, 121Sobotka Marcin, The effectiveness of innovative initiatives, 129Tunkele Sigita, The production cost analysis of high value-added wood products in Latvia, 132
Keywords: none